A secure quantum telephone system - Said, Ressa Suhardiman; Shamsul Shaari, Jesni; Wahiddin, Mohamed Ridza (2009)
The present invention relates to a secure quantum telephone system for two communication parties to communicate securely. Saud secure quantum telephone system comprises of a means for two communicating parties in a secure environment by invoking the basic principle in quantum mechanics and wherein further comprises a system with means which allows two way secure communication by eliminating the need to duplicate the setup